Ricky Ricotta y el poderoso robot contra los meca monos de Marte : la cuarta novela de aventuras - Pilkey, Dav, 1966-; Ontiveros, Martin; Ortiz Gutierrez, Rosario (New York : Scholastic Inc., 2006)
En este libro ilustrado para ninos, el raton Ricky y su Poderoso Robot conocen a un marciano pequeno pero cruel que planea apoderarse de la Tierra con sus monstruosos Meca Monos. Se incluyen instrucciones en como dibujar a los personajes (p. 130-141).
A small mouse and his best friend, a giant flying robot, attempt to save the Earth when an evil Martian monkey and his mechanical creations attack. Includes brief "Flip-o-Rama" section that simulates animation and instructions for drawing six characters.
Translation of: Ricky Ricotta's mighty robot vs. the mecha-monkeys from Mars.
"Scholastic en espanol"--Cover.
In Spanish.
Keywords: Ricotta, Ricky (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Robots -- Juvenile fiction; Monkeys -- Juvenile fiction; Heroes -- Juvenile fiction; Ricotta, Ricky (Fictitious character) -- Fiction; Mice -- Fiction; Robots -- Fiction; Monkeys -- Fiction; Heroes -- Fiction; Humorous stories; Spanish language materials; Humorous fiction; Spanish language materials; 2